2020
DOI: 10.48550/arxiv.2003.06137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radio galaxies and feedback from AGN jets

M. J. Hardcastle,
J. H. Croston

Abstract: We review current understanding of the population of radio galaxies and radio-loud quasars from an observational perspective, focusing on their large-scale structures and dynamics. We discuss the physical conditions in radio galaxies, their fuelling and accretion modes, host galaxies and large-scale environments, and the role(s) they play as engines of feedback in the process of galaxy evolution. Finally we briefly summarise other astrophysical uses of radio galaxy populations, including the study of cosmic ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 371 publications
(516 reference statements)
0
10
0
Order By: Relevance
“…Among the different types of active galactic nuclei (AGN), the radio luminous extragalactic radio sources associated with massive elliptical galaxies and referred to as radio AGN, continue to pose a number of interesting astrophysical questions. These include the triggering of radio AGN activity, the formation of jets squirting out from the AGN with relativistic speeds, its effect on the host galaxy and its subsequent evolution, and relationship of the different radio and optical classification schemes to modes of accretion onto the supermassive black holes which are believed to fuel the AGN activity (e.g., Tadhunter, 2016a;Hardcastle and Croston, 2020). Radio AGN extend in their overall projected linear size from parsec-scales to over a few Mpc, with the largest known radio galaxy so far having a size of about 4.7 Mpc (Machalski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different types of active galactic nuclei (AGN), the radio luminous extragalactic radio sources associated with massive elliptical galaxies and referred to as radio AGN, continue to pose a number of interesting astrophysical questions. These include the triggering of radio AGN activity, the formation of jets squirting out from the AGN with relativistic speeds, its effect on the host galaxy and its subsequent evolution, and relationship of the different radio and optical classification schemes to modes of accretion onto the supermassive black holes which are believed to fuel the AGN activity (e.g., Tadhunter, 2016a;Hardcastle and Croston, 2020). Radio AGN extend in their overall projected linear size from parsec-scales to over a few Mpc, with the largest known radio galaxy so far having a size of about 4.7 Mpc (Machalski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Energy input from radio sources (radio mode feedback) may be important in regulating star formation in massive galaxies and determining the shape of the high end of the galaxy luminosity function and also determining the balance of heating and cooling in the intracluster medium (ICM) (e.g., Croton et al, 2006;Fabian, 2012). AS the PS and CSS sources are propagating through their host galaxies, they can provide examples of radio mode feedback (e.g., Holt et al, 2008;Morganti et al, 2013;Tadhunter, 2016b;Hardcastle and Croston, 2020). Evidence of interaction with the cold component of the interstellar medium in these galaxies via Hi absorption line studies has been reviewed recently by Morganti and Oosterloo (2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, these initial efforts assumed the distortion to be non-relativistic y-distortion and concluded that a cosmological distribution of cocoons with t j =10 7 yr to be severely constrained due to the COBE CMB spectral distortion limit (Fixsen et al 1996). Our calculations suggest that in a ΛCDM universe with the current cosmological parameters, the global averaged < y >∼ 10 −6 for t j = 10 7 yr. Several improvements are in order to make progress -for example, the assumed jet luminosity of their model may be too high compared to the jet luminosity inferred from individual radio galaxies (Hardcastle & Croston 2020). Also, the efficiency factor will not be a constant but a function of dark matter halo mass.…”
Section: Discussionmentioning
confidence: 99%
“…The most plausible heating mechanism is mechanical feedback from the AGN hosted by the cluster -in particular, by the brightest cluster galaxy (BCG; see e.g. reviews by Hardcastle & Croston 2020). Evidence of this hypothesis is found in the X-ray cavities observed in a number clusters, on scales approximately coincident with the lobes of the central radio galaxy (e.g.…”
Section: Introductionmentioning
confidence: 99%